Medicine Card as Innovation Learning in Periodic Table of Elements for Pharmaceutical Vocational Students - ., Zulfah; Statistika, Eka; Sukriani, Eti (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
The innovation in this instruction was the use of medicine card as a learning media of periodic table of elements. This research aimed to know the process of learning conducted by using medicine card and to know the students’ motivation and learning outcomes as the result of the implementation of medicine card in the classroom activity. This research used a quantitative descriptive method. The implementation of the media was conducted in four-fold meetings in Health Vocational School of Sadewa, Yogyakarta, Indonesia. A SWOT analysis was conducted at the beginning of the learning innovation and was followed by the observation and the preparation of material and media. The class activity began with explanations of medicine card games, group divisions, game execution, and confirmation. The final step was evaluated using a questionnaire of motivation and post-test problems. The result of the questionnaire indicated that the students’ motivation was in the good criterion and the learning outcomes of students showed that they had an enough criterion.